Automatability of Occupations, Workers' Labor-Market Expectations, and Willingness to Train - Philipp Lergetporer; Katharina Wedel; Katharina Werner (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study how beliefs about the automatability of workers' occupation affect labor-market expectations and willingness to participate in further training. In our representative online survey, respondents on average underestimate the automation risk of their occupation, especially those in high-automatability occupations. Randomized information about their occupations' automatability increases respondents' concerns about their professional future, and expectations about future changes in their work environment. The information also increases willingness to participate in further training, especially among respondents in highly automatable occupation (+five percentage points). This uptick substantially narrows the gap in willingness to train between those in high- and low-automatability occupations.
Keywords: J24; O33; I29; D83; 330; automation; further training; labor-market expectations; survey experiment; information